Temporary Housing Typologies for Emergency Flood Situations - Rosa , Gabriela Paes; Arruda , Glória Lucia Rodriguez Correia de (Technical and Scientific Journal Green Cities, 2021)
The provision of temporary shelters in cases of flooding is essential in the current context experienced by a large part of the Brazilian population. The weather affects numerous regions of Brazil and causes more and more damage to citizens when combined with urban and social problems such as inadequate channeling of streams and rivers, excessive waterproofing and segregation of communities, leading to the appropriation of wetlands for housing and making them those vulnerable to disasters. Under the circumstances, a bibliographic survey and comparative analysis of the most effective typologies in meeting the human needs hierarchized by Maslow in his book Motivation and Personality (1954) was carried out. For this, technical, spatial, material and qualitative aspects of existing shelters were considered, seeking the ideal combination of attributes for implementation in emergency flood situations. A tendency towards portable and demountable typologies is perceived, with light metal or wood structures, which are considered sustainable and recyclable. Other elements such as the private layout, biophilic design and affective colors are important for the typologies that emerge as a solution to the social problems resulting from the flaws in Brazilian urban planning. KEYWORDS: Floods. Shelters. Temporary.